Tindak Tutur Ilokusi dalam Film “PR-Ku Mung Kowe” Karya Novizal Bahar - Ela Nur Aini; Udjang Pairin (Institut Nalanda, 2024)
Illocutionary speech acts do not only occur in social life but can occur on social media, one of which is in the film “PR-Ku Mung Kowe” by Novizal Bahar which can be seen on the Video.com Bats Channel account or website. The purpose of this research is to discuss the types of illocutionary speech acts used in the movie. The method used in this research is descriptive qualitative method by using data collection techniques in the form of tapping techniques and note-taking techniques. The instruments used in this research are cellphone, laptop, headset, notebook, stationery. Five types of illocutionary speech acts are found in this study, namely assertive illocutionary speech acts, directive illocutionary speech acts, commissive illocutionary speech acts, expressive illocutionary speech acts, and declarative illocutionary speech acts. Assertive illocutionary speech acts are telling and giving understanding, directive illocutionary speech acts are ordering and inviting, commissive illocutionary speech acts are refusing and praying, expressive illocutionary speech acts are saying goodbye and getting angry, and declarative speech acts are giving punishment.